A single point mutation in the hyaC gene affects Pasteurella multocida serovar A capsule production and virulence. (October 2021) - Li, Nengzhang; Feng, Teng; Wang, Yuanlan; Li, Pan; Yin, Yuanyuan; Zhao, Zongling; Hardwidge, Philip R.; Peng, Yuanyi; He, Fang
Abstract: Pasteurella multocida ( P. multocida ) is a Gram-negative bacterium which causes diseases in poultry, livestock, and humans, resulting in huge economic losses. P. multocida serovar A CQ6 (PmCQ6) is a naturally occurring attenuated strain with a thin capsule. Thus, we aimed to explore why this strain is less virulent and produces less capsule compared with P. multocida serovar A strain CQ2 (PmCQ2). Analysis of capsular polysaccharide synthesis genes in PmCQ6 revealed that, compared with PmCQ2, there was only a single point mutation in the initiation codon sequence of the hyaC gene. To test whether this point mutation caused capsular deficiency and reduced virulence, we rescued this hyaC mutation and observed a restoration of capsule production and higher virulence. Transcriptome analysis showed that the hyaC point mutation led to a downregulation of capsule synthesis and/or iron utilization related-genes. Taken together, the results indicate that the start codon mutation of hyaC is an important factor affecting the capsule synthesis and virulence of PmCQ6. Highlights: There was only a single point mutation in capsular synthesis-related hyaC gene of PmCQ6. HyaC rescued mutation showed a restoration of capsule production and higher virulence. HyaC point mutation led to a downregulation of capsule synthesis and iron utilization related-genes.